The Feminist Practices to Fight Sexual Violence: The Case of Marin in Bushnell and Cotugno’s Rules for Being a Girl - Simen, Jennifer Ivane; Riyandari, Angelika; Hartono, Heny (Celt: A Journal of Culture, English Language Teaching & Literature, 2024)
This article explores the feminist practices of fighting against sexual violence conducted by Marin, the main character in Bushnell and Cotugno’s novel, Rules for Being a Girl. The writers used Hall’s (2015), Mulugeta’s (2017), and Hagag Hamed’s (2012) theories to conduct the analysis and interpretation of the perpetrator’s sexual violence and Marin’s actions to fight against sexual violence. The results show that Marin’s teacher, Mr. Bex, committed sexual violence in the form of touching Marin’s cheek, kissing her lips, and intending to touch Marin’s chest. To fight against the sexual violence, Marin reports the case to school administrators, writes in the school newspaper, and starts a feminist book club. Marin's attempts are similar to the practices done by the feminists to confront sexual violence. Her attempts intend to inspire sexual violence victims to speak up and put a fight. As a result, Marin’s fellow students give their testimony and have Mr. Bex kicked out of school. Through her actions and courage, Marin successfully represents herself as a feminist